Trastorno de conducta y su influencia en el rendimiento académico en un paciente de 6 años - Muñoz Campos, Yuri Mariela (2019)
The case study addresses the topic: behavior disorder and its influence on academic performance in a patient. Behavioral disorders are a fairly common affectation in children and are characterized by an alteration in behavior characterized by the violation of social norms and rules, academic performance is a measure of evaluation of the child in their school activities, the objective of this research is to determine if independent variable has influence on the dependent and of what type. The instruments used in the research, Depression Inventory for children of Kovacs, the Luis Font Family Test for the diagnostic evaluation and the use of cognitive behavioral therapy for therapeutic intervention which yielded satisfactorily because once the therapeutic interventions were carried out, the dysfunctional ideas in the child were suppressed and modified, physiological anxiety and negative emotional responses were reduced and socio-family interaction improved